Statistical estimation of regional differences in regions of the Russian Federation in terms of educational potential of young generations - O. V. Potasheva; M. V. Moroshkina (Статистика и экономика)
Present task in providing regional economy with necessary expertsin planning and forecasting of social and economic development is creation of a technique of assessment and monitoring of  educational potential of the population. The statistical data,  characterizing the demographic structure of the young population of  Russia are provided in the paper, regional distinctions from the point  of view of the generation groups are revealed. On this basis the  rating of regions of Russia is calculated, the main valuable and  business characteristics of generational and age groups are  considered and compared. Areas of concern for which the rational  use of generational approach are revealed and the corresponding  recommendations are offered.The purpose of this paper is opportunities’ justification of applyingthe methodology of rating regions in terms of level of the saved-up educational potential by the younger generations to identify and predict the dynamics of qualitative characteristics of labor, as well as the prospects of its use for the management of the  regional development.The methodological basis of the presented paper consists of comparative, economic, statistical and social-cultural methods of  analysis. The space-time base of the results of population censuses  in Russia in 2002 and 2010 by territorial regions of the Russian  Federation, characterizing generational and age structure of youth by the level of the achieved education was collected and statistically  processed for the research. As the part of the presentation of this  paper, the authors proposed an algorithm for comparative analysis of the educational potential of young people by regions of the Russian  Federation and a typological grouping was carried out. The value of  regional differences in regions in terms of the educational potential of young generations is showed in the growing role of in-country  migration of the population, as evidenced by the spatial relationship  with the level of development of the system of higher professional  education in the observed period.Conclusion. The proposed approach and research results can be useful for analysis and planning of social and economic development  of regions by various state bodies at the Federal and regional levels,  as well as by private investors.